2021
DOI: 10.52547/jcbior.2.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum, pneumopericardium pneumothorax and subcutaneous emphysema in Iranian COVID-19 patients

Abstract: Recently, spontaneous pneumomediastinum (PM), pneumopericardium (PP), pneumothorax (PT), and subcutaneous emphysema (SE) were reported as infrequent complications in coronavirus disease 2019 (COVID-19) patients in intensive care (ICU). Here we report these complications in nine Iranian patients of COVID-19. Nine patients with reported PM, PP, PT, and SE in COVID-19 who were hospitalized in Arya hospital, Rasht, Iran, for three months, were followed to record demographic data and clinical characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Patients with COVID-19. Nowadays, the pandemic of coronavirus disease-2019 (COVID-19) is a serious hazard for the healthcare system and patients with primary diseases [62][63][64][65][66][67][68]. It has been revealed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections has the ability to lead to an increased host immune system response and severity of multiple diseases, such as diabetes, hypertension, cardiovascular, and neurological complications [69][70][71][72][73].…”
Section: Mir-146a and Diabeticmentioning
confidence: 99%
“…Patients with COVID-19. Nowadays, the pandemic of coronavirus disease-2019 (COVID-19) is a serious hazard for the healthcare system and patients with primary diseases [62][63][64][65][66][67][68]. It has been revealed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections has the ability to lead to an increased host immune system response and severity of multiple diseases, such as diabetes, hypertension, cardiovascular, and neurological complications [69][70][71][72][73].…”
Section: Mir-146a and Diabeticmentioning
confidence: 99%
“…COVID-19, which emerged in Dec 2019, has caused a concerning epidemic worldwide by SARS-CoV-2 [1][2][3][4][5]. Glycoprotein S or spike protein is the main contributor to virus entry into the host cells and its infection through binding to angiotensin-converting enzyme 2 (ACE2) receptor [6].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID-19) is caused by infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and affects billions of people around the world [ 1 7 ]. SARS-CoV-2 has been increasingly reported to attack not only the respiratory system and lead to respiratory complications [ 8 ] but also the central nervous system (CNS), causing neurological symptoms [ 9 12 ], and progression of multiple cancers [ 13 , 14 ]. According to retrospective investigations, 36.4% of SARS-CoV-2-infected individuals presented neurological manifestations such as acute cerebrovascular diseases, disturbed consciousness, and paresthesia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%